Trends in the Daily Precipitation Categories of Calabria (Southern Italy). (2016) - Caloiero, Tommaso; Coscarelli, Roberto; Ferrari, Ennio; Sirangelo, Beniamino
Abstract: This study presents an analysis of daily rainfall categories over a region of southern Italy using a set of daily homogenous precipitation series for the period 1916–2006. Six daily rainfall categories have been considered: Light, 0–4 mm/day; Light-Moderate, 4–16 mm/day; Moderate-Heavy, 16–32 mm/day; Heavy, 32–64 mm/day; Heavy-Torrential, 64–128 mm/day; Torrential, 128-up mm/day. Results showed that Light-Moderate, Moderate-Heavy and Heavy rainfall are the main contributors to the total annual rainfall. Moreover, a trend analysis through the Mann-Kendall test showed a decreasing trend of the higher categories and an increasing trend of the weaker categories.